Cavity electromagnetically induced transparency via spontaneously generated coherence. Issue 17 (25th September 2017) - Tariq, Muhammad; Ziauddin; Bano, Tahira; Ahmad, Iftikhar; Lee, Ray-Kuang
Abstract: A four-level N -type atomic ensemble enclosed in a cavity is revisited to investigate the influence of spontaneous generated coherence (SGC) on transmission features of weak probe light field. A weak probe field is propagating through the cavity where each atom inside the cavity follows four-level N -type atom-field configuration of rubidium ( 85 R b ) atom. We use input–output theory and study the interaction of atomic ensemble and three cavity fields which are coupled to the same cavity mode. A SGC affects the transmission properties of weak probe light field due to which a transparency window (cavity EIT) appears. At resonance condition the transparency window increases with increasing the SGC in the system. We also studied the influence of the SGC on group delay and investigated magnitude enhancement of group delay for the maximum SGC in the system.